TPACK Towards ICT Integration: Does Creativity Have a Moderating Effect? - Khresna Bayu Sangka; Mintasih Indriayu; Colin Mackenzie; Villa Santika (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2022)
The purpose of this study was to examine an effect of technological pedagogical and content knowledge (TPACK) on information and communication technology (ICT) integration in Indonesia with moderated by creativity. The data for this study was taken from respondents consisting of 405 Economic Teachers using voluntary sampling techniques. The survey method for this quantitative research was conducted by distributing questionnaire to respondents and were developed according to current condition and have fulfilled the requirements for confirmatory analysis test. Inferential analysis using a structural equation model analysis technique with moderating effect shows that TPACK has a positive and a significant effect on ICT integration (β = 0.143, p = 0.008<0.05). The interaction of creativity with TPACK has no positive and no significant effect on ICT integration (β = -0.037, p = 0.238>0.05). The creativity has a positive effect and significant effect on ICT integration (β = 0.513, p = 0.00<0.05). Based on these study results, variable creativity is not a pure moderator rather moderator predictor which means it acts as a predictor or mediator variable. This study can provide useful information that can be used as a stakeholder in providing teachers with opportunities to increase their creativity or as the foundation for future research into measuring teacher creativity as a predictor or mediator variable.